Sedimentological, mineralogical, and biogeochemical characteristics in the Aleutian Trench and adjacent abyssal plains - Sindlev, Marco B; Balmonte, John Paul; Wenzhöfer, Frank; Xiao, Wenjie; Stief, Peter; Oguri, Kazumasa; Tsuchiya, M; Yokoyama, Yusuke; Rudra, Arka; Canfield, Donald E; Sanei, Hamed; Brandt, Angelika; et al. (PANGAEA, 2025)
To understand sedimentological, mineralogical and benthic biogeochemical characteristics of the Aleutian Trench study area, datasets of grain size fractions, porosity and density, ratio of quartz to plagioclase, total organic carbon (TOC), δ13C, Δ14C, Chlorophyll a (Chl a), total photopigments, hydrogen and oxygen indices (H- and O-indices), dissolved inorganic carbon (DIC), ammonium (NH4+), 210Pbex, 137Cs and 210Pbex inventory were analysed from retrieved marine sediment core collected from 13 different stations. The marine sediment cores were retrieved using a Multiple Corer (MUC) during the Aleutian Trench Biodiversity Studies (AleutBio) expedition (RV Sonne, SO293), which took place from 24/07/2022 to 06/09/2022. Retrieved sediment cores were generally sectioned in 1 cm intervals in the upper 10 cm of core depth, 2.5 cm intervals from 10-20 cm and ultimately 5 cm intervals for the remaining core interval. Sediment slices were generally stored at -20 °C until subsequent analysis. All measurements were processed following standardized protocols described in Sindlev et al. (in review) and provides a baseline for investigating benthic processes and depositional characteristics in the study area.
Keywords: Grain Size; Hadal trench; organic matter; Pigments; sediment